Efectividad de la musicoterapia en las habilidades sociales de niños con trastorno del espectro autista - Tejada Arana, Carolina Andrea (2024)
Deficiency in social skills is a characteristic factor in autism spectrum disorder (ASD). In children, this has a great impact in various areas due to the inevitability of constantly finding themselves in social environments. Taking this situation into account, the importance of finding a treatment that allows working on such aspects is highlighted. Thus, the aim of the study is to determine the effectiveness of music therapy (MT) on social skills (SS) of children with ASD. A bibliographic search was carried out in databases such as Web of Science, SpringerLink, Scopus and ScienceDirect, and 10 articles that met the proposed criteria were identified. As result, it was found that most of studies (8) indicate that MT is an effective intervention for the development of SS such as visual attention, joint attention, gestures, commitment, among others, in children with ASD. However, two other texts point out that, although changes were observed after the sessions, they were not necessarily significant. In conclusion, it is necessary to continue investigating the relationship between such variables to determine the effectiveness of the intervention. It should be noted that improvements were observed when TM was applied as part of a comprehensive treatment.